1997
DOI: 10.1016/s0042-6989(96)00224-6
|View full text |Cite
|
Sign up to set email alerts
|

Local Changes in Eye Growth induced by Imposed Local Refractive Error despite Active Accommodation

Abstract: We have tested whether defocus imposed on local retinal areas can produce local changes in eye growth, even if accommodation is available to clear part of the imposed defocus. Hemi-field lenses were attached to little leather hoods that were worn by young chickens from day 11-15 post-hatching. The lens segments defocused either the nasal or the temporal visual field, or covered the full field. We found that negative lenses (-7.5 D) were incompletely compensated in all three cases but caused significant myopia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(120 citation statements)
references
References 18 publications
3
115
1
1
Order By: Relevance
“…[10][11][12][13] More recently, studies on infant monkeys suggest that the peripheral retina can play an important role in modulating overall eye growth. [14][15][16][17][18][19] In contrast, Schippert and Schaeffel 20 found that chicks reared with lenses having clear central apertures remained emmetropic, showing no evidence of failure of emmetropization when peripheral refraction was artificially changed.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] More recently, studies on infant monkeys suggest that the peripheral retina can play an important role in modulating overall eye growth. [14][15][16][17][18][19] In contrast, Schippert and Schaeffel 20 found that chicks reared with lenses having clear central apertures remained emmetropic, showing no evidence of failure of emmetropization when peripheral refraction was artificially changed.…”
Section: Discussionmentioning
confidence: 99%
“…As shown first in chickens by Wallman et al, 44 when visual manipulations that influence eye growth (eg, form deprivation, 44,45 myopic defocus 46,47 or hyperopic defocus 47,48 ) are imposed across only half the visual field, the resulting alterations in refractive error and vitreous chamber growth are restricted to the treated hemi retina. For example, when form deprivation, a strong stimulus for axial growth, is imposed across the entire visual field, the eye becomes more prolate in shape with the greatest increase in vitreous chamber depth found in the central retina with smaller symmetrical increases in the nasal and temporal retina (Figure 2 left).…”
Section: Refractive Development Is Regulated In a Locus-specific Mannermentioning
confidence: 93%
“…[1][2][3] Local retinal mechanism refers to a condition that local retina could minimize the image degradation on the corresponding retinal location by changing the axial eye growth rate. [4] The homeostatic control signals of the eyes growth try to keep the image sharply focused on the retina ("grow to clarity" model).…”
Section: Control Of Ocular Growthmentioning
confidence: 99%